2021
DOI: 10.1111/1365-2656.13428
|View full text |Cite
|
Sign up to set email alerts
|

A time‐lagged association between the gut microbiome, nestling weight and nestling survival in wild great tits

Abstract: This article has been accepted for publication and undergone full peer review but has not been through the copyediting, typesetting, pagination and proofreading process, which may lead to differences between this version and the Version of Record. Please cite this article as

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(56 citation statements)
references
References 106 publications
5
50
1
Order By: Relevance
“…A small number of studies have explored interactions between GM composition and host infection in the wild [ 26 , 30 , 31 ], however, there is conflicting evidence over whether, and how, GM diversity influences host condition. For example, one study on great tits ( Parus major ) demonstrated a positive relationship between GM species richness and nestling body mass [ 32 ], while other studies on the same (and other) species have shown the opposite effect, suggesting that, although the GM can contribute to host nutrition and immunity, there could be costs to maintaining a diverse microbiome in young birds [ 33 , 34 ]. The relationship between particular component taxa in the GM and host body condition is complex and has been shown to vary across host species [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…A small number of studies have explored interactions between GM composition and host infection in the wild [ 26 , 30 , 31 ], however, there is conflicting evidence over whether, and how, GM diversity influences host condition. For example, one study on great tits ( Parus major ) demonstrated a positive relationship between GM species richness and nestling body mass [ 32 ], while other studies on the same (and other) species have shown the opposite effect, suggesting that, although the GM can contribute to host nutrition and immunity, there could be costs to maintaining a diverse microbiome in young birds [ 33 , 34 ]. The relationship between particular component taxa in the GM and host body condition is complex and has been shown to vary across host species [ 33 ].…”
Section: Introductionmentioning
confidence: 99%
“…We are only aware of two studies that have investigated the link between GM characteristics and survival in wild vertebrate species. In great tit nestlings, a negative, time-lagged association between GM alpha diversity and body mass was identified; while, separately in the same study, a reduced body mass was associated with a lower probability of successful fledging [33]. Similarly, in a study on adult blue tits (Cyanistes caeruleus), reduced species richness and the presence of pathogenic Campylobacter species in the GM was associated with reduced annual survival, although gel electrophoresis was used to assess bacterial community structure in this instance, which limited further resolution [34].…”
Section: Introductionmentioning
confidence: 73%
“…Previous studies investigating the relationship between GM alpha diversity and individual condition have shown mixed results, with both positive [23,31,77] and negative [32,33,78] relationships, as well the absence of an association [79,80] being identified across various wild and captive vertebrate host species. However, these studies often focus on early life stages, despite the fact that body mass can be an important predictor of fitness in adult individuals [63,81,82].…”
Section: Gut Microbiome Diversity and Body Conditionmentioning
confidence: 91%
See 2 more Smart Citations